Analysis of MPLS-TP Network for Different Applications - Suhaimy, N.; S. H. M. W. Ahmad, W.; A M. Radzi, N.; Abdullah, F.; Z. Jamaludin, M.; N. Zakaria, M. (International Journal of Engineering and Technology, 2018)
In the perspective of Multiprotocol Label Switching â€“ Transport Profile (MPLS-TP) network, a reliable framework architecture or mechanism needs to be ascertained by comparing the results obtained through implementation of previously proposed scheme towards the network. This is important in order to implement an efficient system for different types of applications or services. Various results are reviewed and analyzed from the related works followed by detail discussions based on their proposed objectives. The analyses shown that most applications of MPLS-TP have been utilized for protection, followed by Operations, Administration and Maintenance (OAM), fairness and congestion control. This is due to the mission-critical operational service of protection which require us to meet the standard protection switching time of 50 ms.Â Â Â